La administración de fondos privados de pensiones de Perú frente a las crisis financieras internacionales (1993-2013) - Flórez G., Wilmer (2014)
The levels of risk generated by the financial crisis could affect substantially the economic and social well-being of contributors to a pension fund people whether this private or public. The aim of this article is the study of the administration of private funds pensions of Peru and the measurement of its relationship with the seven international financial crises developed between 1993 and 2013: subprime mortgage Crisis, Mexican, Asian, Russian, Brazilian, Argentine, and Europe’s crisis. A correlational descriptive study was conducted to test the bonds of relationship between the yield of Peru pension funds and stock indices of economies in crisis according to each case, and its corresponding temporality. To determine the financial efficiency of the Peruvian pension funds investments, it was necessary to calculate the index of Sharpe’s main Latin America pension funds whereas horizons of five, ten and fifteen years, for greater perspective. It was found that administration of pension funds had a significant correlation with the crises in Asia, Russia, Brazil, Argentina, USA and the crisis of Europe, except the Mexican crisis. The financial crisis with the highest degree of linear Association (Dear by the Pearson coefficient) and greater adverse impact was the mortgage crisis subprime United States. It was found that the results of efficiency financial (according to the Sharpe index) of pension funds in Peru were below the average in the region.